Comparison Analysis Performance Of Gasoline Engine Using Active And Non-Active I-Vtec System - Hidayat, Faizal; , Ir. Subroto, M.T; , Nur Aklis, S.T., M.Eng (2013)
Nowadays, many demands from consumers to have a car with powerful engine and low of gasoline so vehicle manufactures think how to make engine like that. Vehicle manufactures develop technology which can increase of performance and the engine can have a great power and torque. Intellegence Variable Timing and Lift Electronic Control (i-VTEC) can be used to problem solve above because it can control timing valve. I-VTEC can increase engine performance that can make the gasoline engine will increase power and torque. Research target that is to know influence variable valve timing to engine performance at four stroke engine 1497cc. Research uses four stroke engine with two types of engine with active i-VTEC and engine with non-active i-VTEC. Two types of four stroke engine will testing above engine dynamometer. Calculation is conducted after got data of testing result. Base testing and analysis can be concluded that engine use active i-VTEC have higher performance than engine with non-active i-VTEC. From dynamometer test was get maximum torque from engine use i-VTEC is 148 Nm at 5000 rpm and maximum torque from engine with non-active i-VTEC is 142 Nm at 5000 rpm. Maximum power from engine use active i-VTEC is 120.6 BHP at 6500 rpm and maximum power from engine with non-active i-VTEC is 115.2 BHP at 6500 rpm. IVTEC organizes timing of valve which can make overlapping on the machine. Overlapping make number of air-fuel mixture in combustion chamber will increase which can make performance will increases